The “great frustrated historian”. Machiavelli according to José Luis Romero: Maquiavelo según José Luis Romero - Cavallero, Constanza (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2021)
This work focuses on the reading and analysis of the work of Nicholas Machiavelli made by the Argentinian historian José Luis Romero (1909-1977) in several of his historical and historiographical writings. It attends, particularly, to the assessment that Romero has made of the famous Florentine thinker as historian. From this perspective, it will be studied the impact of the Machiavellian work on the thought and intellectual work of the Argentinian academician. This work seeks to show that Machiavelli was, for the aforementioned author of the 20th Century, a source of inspiration, a master in the analysis of  “the real reality” and an example of commitment to public affairs. However, Machiavelli's work entailed a strong warning for him: there must be proper balance between academic rigor and political commitment, between the historian's own claim to truth and the citizen's ideological position.
Keywords: Machiavelli; Romero; historiography; History; Politics